2020
DOI: 10.1167/iovs.61.10.35
|View full text |Cite
|
Sign up to set email alerts
|

Risuteganib Protects against Hydroquinone–induced Injury in Human RPE Cells

Abstract: PURPOSE. Cigarette smoking has been implicated in the pathogenesis of AMD. Integrin dysfunctions have been associated with AMD. Herein, we investigate the effect of risuteganib (RSG), an integrin regulator, on RPE cell injury induced by hydroquinone (HQ), an important oxidant in cigarette smoke. METHODS. Cultured human RPE cells were treated with HQ in the presence or absence of RSG. Cell death, mitochondrial respiration, reactive oxygen species production, and mitochondrial membrane potential were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
3
12
0
Order By: Relevance
“…Our results showed that cells incubated with HQ had marked disorganization of the mitochondrial network compared with control RPE cells (Figure 2A). Further, HQ exposure led to a significant reduction in the mitochondrial membrane potential of human RPE cells (Figure 2B), in agreement with recent studies [28]. While H 2 O 2 -treated cells also showed some changes in the mitochondrial network morphology (Figure 2A), the mitochondrial membrane potential remained unaffected after treatment with up to 500 µM H 2 O 2 (Figure 2B), confirming the relative resistance of RPE cells against H 2 O 2 -induced damage.…”
Section: Hq-induced Mitochondrial Dysfunctionsupporting
confidence: 92%
“…Our results showed that cells incubated with HQ had marked disorganization of the mitochondrial network compared with control RPE cells (Figure 2A). Further, HQ exposure led to a significant reduction in the mitochondrial membrane potential of human RPE cells (Figure 2B), in agreement with recent studies [28]. While H 2 O 2 -treated cells also showed some changes in the mitochondrial network morphology (Figure 2A), the mitochondrial membrane potential remained unaffected after treatment with up to 500 µM H 2 O 2 (Figure 2B), confirming the relative resistance of RPE cells against H 2 O 2 -induced damage.…”
Section: Hq-induced Mitochondrial Dysfunctionsupporting
confidence: 92%
“…Treatment with RSG alone was not evaluated because of the following: (1) it had a nonsignificant effect on cell viability and (2) previous study found it had a minimal effect on the transcriptome of human RPE cells. 24 RSG pretreatment followed by RSG and H 2 O 2 cotreatment was also not evaluated since both RSG pretreatment regimens showed comparable protection. All samples had excellent RNA quality and sequencing quality ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 22 , 23 In a preclinical model of human RPE cells stressed with cigarette smoke toxin, RSG treatment reduced cell death and ROS level, upregulated cytoprotective genes, and improved mitochondrial bioenergetics and metabolic activity. 24 In RPE cells constructed to contain AMD donor mitochondria, RSG exposure reduced the expression of apoptosis and angiogenesis genes. 25 …”
Section: Introductionmentioning
confidence: 99%
“…In human donor RPE cells, risuteganib was found to protect cells by reducing ROS level, upregulating cytoprotective heme oxygenase-1 protein level, and regulating genes in multiple disease-relevant pathways including inflammation, cell proliferation, cell adhesion and migration. 15 In RPE cells containing mitochondria derived from AMD patients, risuteganib exposure was associated with reduced expression of genes associated with apoptosis (BAX), angiogenesis (VEGFA) and integrin function (ITGB1). 16 Pharmacokinetics studies found risuteganib has a long half-life in the retina after intravitreal injection, whereas ex vivo studies suggest the peptide may be specifically localized to the RPE cells, where it may play a role in preserving and reversing the diseased cellular state.…”
Section: Introductionmentioning
confidence: 99%
“…17 This is further supported by studies from multiple labs that demonstrated improved mitochondrial bioenergetics and metabolic activity after risuteganib treatment, indicating potential reactivation of patient RPE with diminished mitochondrial function. 15,17,18 Studies of other antioxidants have also demonstrated reduction in retinopathy and improvement in visual parameters in animal models, [19][20][21] suggesting pro-mitochondrial therapeutics can lead to both morphological and functional improvements. Collectively, pre-clinical studies demonstrated that risuteganib has cytoprotective, antiinflammatory, and pro-mitochondria properties, which make it a potential candidate for use in the treatment of nonexudative AMD.…”
Section: Introductionmentioning
confidence: 99%